The digital economy and the European labour market - Urbaniec, Maria (Economist) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"With a focus on the European labour market, this book seeks to understand how digital transformation affects changes in employee-employer relations. These consequences include shifts in job security and job flexibility as well as alternative work arrangements in the digital economy. This phenomenon has both positive and negative implications for employees and employers. The book presents a theoretical, conceptual and empirical analysis of employment relations in the digital economy, which are manifested, among others, in flexible or non-standard forms of employment, contract work and a radical shift from position-based to skill-based work. The approach taken in the book provides researchers and students of economics, business and other social sciences with an overview of interdisciplinary theoretical and conceptual perspectives and frameworks on labour market and employment relations. In particular, it presents a comprehensive range of research on flexible forms of employment in the digital economy. The range of issues covered is also tailored to business practitioners who wish to understand the ongoing changes in employment relations and the emergence of new forms of work as a result of digital transformation. It will also be of value to representatives of labour market institutions involved in implementing new forms of work and employer-employee relationships in Industry 4.0"--
Keywords: Labor market -- Europe; Information technology -- Economic aspects -- Europe; Employees -- Effect of technological innovations on -- Europe; Industrial relations -- Europe; Europe -- Economic conditions -- 21st century; BUSINESS & ECONOMICS / Labor; BUSINESS & ECONOMICS / Economic Conditions